Potensi Pariwisata Dan Strategi Pengembangan Desa Wisata Sukajadi di Kabupaten Bogor - Dina Mayasari Soeswoyo (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2021)
This study identifies the potential of tourism products in Sukajadi Village Bogor Regency based on ten (10) tourism components as well as its development strategy, which is currently included in the category of a newly developing tourist village. The results of this research are aggressive and serious development strategies in all aspects of the tourism component, namely increasing the quality and diversification of tourist attractions and activities, accessibility, improving the quality and quantity of tourism amenities, improving the quality of human resources & institutions, community support, land use, tourism industry cooperation, as well as marketing aspects. This research type is a descriptive qualitative with a case study exploratory approach. Primary data is obtained from direct observation and interviews with key informants, namely Pokdarwis and the Village Head, while secondary data is the result of literature studies and research documentation. The analysis technique of this research uses SWOT analysis and Matrix, analysis of the work program of the vision for tourism development of the Bogor Regency Government which refers to local government master plan for tourism development (RIPPARDA), and also analysis of the Cleanlines, Health, Safety and Environmental Sustainability (CHSE) guidelines.